PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJAKARYAWAN PT. PLN PERSERO AREA KUPANG - Merry S Limbong; Tarsisius Timuneno; Rolland E Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2019)
The research method used is an associative method that uses questionnaires as a data collection tool that is distributed throughout the respondents. The population in the study were all employees of PT. Kupang Area PLN. The number of samples taken was 43 respondents. As for analyzing and calculating the overall effect of independent variables Leadership Style and motivation on employee performance dependent variables that are processed using a computer program spss for window. The results of multiple linear regression analysis show that hypothesis testing proves that partially variable leadership style has a positive and significant effect on the performance of employees of PT. Kupang Area PLN, while the motivation variable does not affect employee performance. Simultaneous testing shows that the independent variable Leadership Style and motivation affect employee performance. Kupang Area PLN. Keywords: Leadership Style, Motivation and Performance